2022
DOI: 10.1155/2022/8995358
|View full text |Cite
|
Sign up to set email alerts
|

5-Year Survivorship and Outcomes of Robotic-Arm-Assisted Medial Unicompartmental Knee Arthroplasty

Abstract: Purpose. While unicompartmental knee arthroplasty (UKA) has demonstrated benefits over total knee arthroplasty (TKA) in selected populations, component placement continues to be challenging with conventional surgical instruments, resulting in higher early failure rates. Robotic-arm-assisted UKA (RA-UKA) has shown to be successful in component positioning through preop planning and intraop adjustability. The purpose of this study is to assess the 5-year clinical outcomes of medial RA-UKA. Methods. This study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Matassi et al 16 reported that robotic-assisted UKA can help doctors with low hand counts improve the accuracy of the prosthetic position and reduce deviation rates. 16 Gaudiani et al 15 and Zhang et al 14 also found that robotic-assisted medial UKA helped to improve the accuracy of prosthetic positioning and recovery of joint function. However, these studies did not investigate the degree to which prosthesis position deviation affected the UKA survival rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matassi et al 16 reported that robotic-assisted UKA can help doctors with low hand counts improve the accuracy of the prosthetic position and reduce deviation rates. 16 Gaudiani et al 15 and Zhang et al 14 also found that robotic-assisted medial UKA helped to improve the accuracy of prosthetic positioning and recovery of joint function. However, these studies did not investigate the degree to which prosthesis position deviation affected the UKA survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…13 In recent years, some studies have found that robotic-assisted UKA can improve the positioning of the prostheses, thereby improving their clinical efficacy and reducing revision rates. [14][15][16] To the best of our knowledge, there are no current reports on the impact of UKA prosthesis position deviation on the survival rate. Therefore, in this study we sought to retrospectively evaluate the clinical data of 407 patients who underwent UKA in a single joint arthroplasty centre with long-term follow-up (five to 11 years), and to analyze the clinical efficacy of the procedure and the risk factors for UKA failure.…”
Section: Introductionmentioning
confidence: 99%